2022
DOI: 10.3390/ani12141741
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Evolution of Gobiidae: A Genetic Exploration

Abstract: The Gobiidae family occupy one of the most diverse habitat ranges of all fishes. One key reason for their successful colonization of different habitats is their ability to adapt to different energy demands. This energy requirement is related to the ability of mitochondria in cells to generate energy via oxidative phosphorylation (OXPHOS). Here, we assembled three complete mitochondrial genomes of Rhinogobius shennongensis, Rhinogobius wuyanlingensis, and Chaenogobius annularis. These mitogenomes are circular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The overall AT content of the heavy strands of these two mitochondrial genomes was higher than the GC content, indicating AT-rich characteristics. The base compositions were skewed similarly to those of other vertebrate mitochondrial genome sequences [41][42][43]. The AT content was higher than the GC content in most of the mitochondrial genomes of otters (Table 4).…”
Section: Discussionmentioning
confidence: 78%
“…The overall AT content of the heavy strands of these two mitochondrial genomes was higher than the GC content, indicating AT-rich characteristics. The base compositions were skewed similarly to those of other vertebrate mitochondrial genome sequences [41][42][43]. The AT content was higher than the GC content in most of the mitochondrial genomes of otters (Table 4).…”
Section: Discussionmentioning
confidence: 78%
“…For example, the microsatellite characteristics of 19 Gobiidae fish provided powerful support for microsatellite development in Gobiidae [12]. Complete mitogenome assembly in three Gobiidae fish demonstrated that the evolution of mitochondrial genome protein-coding genes (mtDNA PCGs) was crucial to Gobiidae adaptability [13]. Although the Gobiidae family contains more than 2000 species [1], only 18 species' genomes have been published (https://www.ncbi.nlm.nih.gov/genome/?term=Gobiidae, accessed on 7 March 2024).…”
Section: Introductionmentioning
confidence: 99%
“…The non-synonymous/synonymous substitution rate (dN/dS) is often used to calculate the evolution of 13 mtDNA PCGs 18 , 19 . Thus, we calculated the rate of evolution of Bovidae mitochondrial genes using dN/dS.…”
Section: Introductionmentioning
confidence: 99%